THE INFLUENCE OF THE USE OF HIGH HEELED SHOES IN THE CURVATURES OF THE SPINE (Fiep Bulletin - online, 2015)
The aim of this study was to determine the influence of wearing high heeled shoes over the spinal arrangement. Twenty healthy women (age = 24,0 ± 4,0 years and BMI = 21,1  2,0 kg/m²) were valued. Posture was determined by photometry in two instants, i.e., with (9.0 cm) and without high heeled shoes. The spinal processes of C7, T12, L5 and the acromium were identified and marked over the skin. The used methods has been long applied by Christie et al. (1995) and Braun & Amundson (1989). Shoulder angle increased (p
Keywords: Postural variation; vertebral column; posture.